Enhancing English Vocabulary Mastery through Social Media Exposure: A Quasi-Experimental Study of Generation Z Learners - Roni; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study investigates the effectiveness of social media exposure in enhancing English vocabulary mastery among Generation Z learners. The rapid growth of digital technology has positioned social media platforms such as TikTok, Instagram, and YouTube as prominent sources of informal language input, particularly for digitally native students. Grounded in the theory of Comprehensible Input, this research examines whether structured exposure to English-language content on social media can significantly improve students’ vocabulary mastery. This study employed a quantitative approach using a quasi-experimental design with a one-group pre-test and post-test model. The participants consisted of 20 Generation Z students from the English Education Department at a regional university in Indonesia. Data were collected through a vocabulary test administered before and after a seven-day social media exposure program, as well as a questionnaire measuring students’ engagement with English-language content on social media. The data were analysed using paired sample t-test and simple linear regression with the assistance of SPSS. The findings revealed a statistically significant improvement in students’ vocabulary mastery after the treatment. The mean score increased from 50.75 in the pre-test to 82.25 in the post-test, with a significance value of 0.000 (p < 0.05). Furthermore, the regression analysis indicated that social media engagement had a significant positive effect on vocabulary mastery, explaining 37.8% of the variance in post-test scores (R² = 0.378, p = 0.004). These results suggest that higher levels of engagement with English-language content on social media are associated with better vocabulary outcomes. social media exposure can serve as an effective supplementary tool for enhancing English vocabulary mastery among Generation Z learners. When used purposefully, social media provides authentic, multimodal, and contextual language input that aligns with learners’ digital habits and supports vocabulary acquisition beyond the traditional classroom setting.